Asymmetric Effects of Oil Prices and Global Financial Factors on the Saudi Stock Market: A NARDL Approach - Alalmai, Somaiyah (International Journal of Economics and Financial Issues, 2025)
This research paper examines the asymmetric effects of key macroeconomic and international stock market indices on the “Saudi stock market (TASI).” This research employs a “non-linear autoregressive distributed lag (NARDL) model” that incorporates monthly information from 2000 to 2024 to inspect the impacts of “oil prices (WTI), interest rates, exchange rates (REER), oil production, inflation, and global equity markets (the S&P 500 and the Shanghai Composite).” The empirical evidence reveals significant long-run asymmetries, particularly from positive oil production shocks, which appear to have a strong and positive impact on “TASI.” In the short run, currency depreciation and declines in oil prices also lead to improved market returns. In contrast, factors such as interest rates, inflation rates, and global stock indices show limited influence. Overall, the findings shed light on the central role of oil and exchange rate dynamics in shaping the Saudi financial market. These insights offer meaningful findings for regulators and investors seeking to promote market stability and navigate external shocks in an increasingly interconnected global economy.